The frequency of metabolically healthy and unhealthy phenotypes in women aged 25–44 years with different levels of thyroid-stimulating hormone, prolactin, leptin - V. I. Alferova; S. V. Mustafina; O. D. Rymar; S. M. Voevoda; L. V. Shcherbakova; E. M. Stakhneva; D. V. Denisova (Сибирский научный медицинский журнал, 2023)
Reports that the risk of developing cardiovascular diseases in obesity is not the same, led to the allocation of metabolically healthy and unhealthy phenotypes (MHP and MUHP), this concept is based on the ability of adipose tissue to produce a number of adipokines, one of which is leptin. Hormones such as thyroid-stimulating hormone (TSH) and prolactin (PRL) are interesting from the point of view of their effect on metabolism. Aim of the study was to investigate the prevalence of MHP and MUHP in young women with different body mass index (BMI) and hormonal status (TSH, PRL, leptin) in different phenotypes. Material and methods. A group of women (n = 655) was selected from a representative sample of the Novosibirsk population aged 25–44 to study clinical and laboratory parameters. The design is a cross – sectional, observational, single – centre study. IDF, 2005 and NCEP ATP III, 2001 criteria were used to evaluate the MHP and MUHP. Results and discussion. The prevalence of MUHP in young women in Novosibirsk was 22.3 %, MHP – 77.7 % according to IDF, 2005; according to NCEP ATP III, 2001 – 13.1 and 86.9 %, respectively. The prevalence of MUHP increased with increasing BMI from 4.0 to 72.0 % according to IDF, 2005 and from 2.3 to 58.0 % according to NCEP ATP III, 2001, respectively. In obese women, MUHP was detected twice as often as MHP – 72 and 28 % according to IDF, 2005, 58 and 42 % according to NCEP ATP III, 2001. TSH and PRL do not provide information about metabolic health in young women. Leptin content is associated with BMI. The threshold value of the leptin level was 18.3 ng/ml with maximum sensitivity and specificity (Se = 53.3 %, Sp = 81.5 %), 14.5 ng/ml with equal sensitivity and specificity (Se = 65.7 %, Sp = 65.7 %). The area under ROC curve (AUC) for diagnosis of MUHP was 0.727 (SE = 0.029, p < 0.0001). Conclusion. The frequency of MHP in young women decreases with increasing BMI. MUHP is 3.5 times less common than MHP according to IDF criteria, 2005. TSH and PRL are not associated with the metabolic phenotype in young women. A leptin level more than 18.3 ng/ml has been identified as one of the markers for the recognition of MUHP in women aged 25–44 years, regardless of BMI.